IMPLEMENTATION USING DATA SECURITY XOR encryption MODEL ALGORITHM - Hariyanto Hariyanto Hariyanto (Majalah SIKOMTEK, 2006)
The problem of data security is a problem frequently faced by computer users especially ifthe data is communicated with the other computer, where data needs to be protected to avoidabuse by people who are not entitled the data. One of the things that are important in ensuringthe confidentiality of the data is to use encryption techniques. Encryption dalah a process thatchanges a code of conduct that can be understood (plaintext) into a code incomprehensible(not readable / ciphertext)). One method used for the encryption algorithm is the ExclusiveOR logical operators (XOR) the plaintext data which is converted into ASCII code stored inbinary form (ciphertext) so that data can not be read without knowing the decryption key.XOR encryption methods can be implemented through various programs, one of them usingVisual Basic software, allowing you seen changes in the data (encryption) from plaintext intociphertext and decrypt the data through changes back into plaintext.